Experimental Study on Hydraulic Pressure Requirements for Stamping Aluminum Sheets of 2–3 mm Thickness - chitchai outhaile, chitchai_Hydraulic (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The manufacturing industry in Lao PDR often relies on manual mechanical presses, which result in inconsistent production, a defect rate exceeding 20%, and significant safety risks. This study aims to identify the optimal hydraulic pressure for stamping aluminum sheets with thicknesses of 2 mm and 3 mm, in order to enhance production efficiency and address the limitations of manual processes. An experimental approach was employed, using a hydraulic press at varying pressure levels to evaluate the quality of the stamped coins. The results indicate that for 2 mm thick aluminum sheets, an optimal pressure of 8 bar achieved a 100% success rate. For 3 mm thick sheets, a pressure of 7 bar yielded a 95% success rate. These findings demonstrate that replacing manual stamping methods with a properly calibrated hydraulic system significantly improves product consistency, reduces material waste, and enhances workplace safety.